2002
DOI: 10.1023/a:1015854415746
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Breast Cancer-Restricted Antigens by Antibody Screening of SKBR3 cDNA Library Using a Preselected Patient's Serum

Abstract: Screening of a breast cancer cDNA library from SKBR3 human breast cancer cells by SEREX (serological analysis of cDNA expression library) using a preselected serum from a breast cancer patient revealed 13 genes, two of which, INT-MI-1 and INT-MI-2, encode novel gene products, while the remaining 11 genes and their products are identical with or highly homologous to known GenBank entries. Immunoscreening of the 13 clones using 20 allogeneic sera from breast cancer patients and 20 samples from age- and gender-ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 30 publications
3
36
0
Order By: Relevance
“…Recent studies using a gene expression profiling technique, have shown that the gene for osteopontin a secreted integrin-binding ECM glycoprotein, is differentially expressed during colon cancer progression (Agrawal et al, 2002). In keeping, we found that glycoprotein fibulin-1 (FBLN-1), a cysteine-rich, calcium-binding ECM and plasma molecule (Argraves et al, 1990), is aberrantly overtranscribed in epithelial tumor cell lines and breast surgical specimens, and that the protein is accumulated in the breast cancer-associated stroma, as detected immunohistochemically (Forti et al, 2002). Augmented expression of FBLN-1 has been also reported in human ovarian cancer cells stimulated with estrogens, and the resulting overexpression facilitated ovarian tumor cell invasion and progression (Clinton et al, 1996;Moll et al, 2002).…”
Section: Oncogenic Signals Of Ecm Componentssupporting
confidence: 57%
See 1 more Smart Citation
“…Recent studies using a gene expression profiling technique, have shown that the gene for osteopontin a secreted integrin-binding ECM glycoprotein, is differentially expressed during colon cancer progression (Agrawal et al, 2002). In keeping, we found that glycoprotein fibulin-1 (FBLN-1), a cysteine-rich, calcium-binding ECM and plasma molecule (Argraves et al, 1990), is aberrantly overtranscribed in epithelial tumor cell lines and breast surgical specimens, and that the protein is accumulated in the breast cancer-associated stroma, as detected immunohistochemically (Forti et al, 2002). Augmented expression of FBLN-1 has been also reported in human ovarian cancer cells stimulated with estrogens, and the resulting overexpression facilitated ovarian tumor cell invasion and progression (Clinton et al, 1996;Moll et al, 2002).…”
Section: Oncogenic Signals Of Ecm Componentssupporting
confidence: 57%
“…FBLN-1 might also promote tumor cell extravasation, since this protein has been shown to increase platelet adhesion by interacting with fibrinogen (Tran et al, 1995). By analysis of recombinant cDNA expression library using breast cancer patients' sera, we detected humoral immunity to FBLN-1 (Forti et al, 2002), indicating that altered ECM components can also be immunogenic in tumor patients.…”
Section: Oncogenic Signals Of Ecm Componentsmentioning
confidence: 99%
“…Application of these techniques has led to the identification of new targets for gene therapy of human neoplasms. Among these techniques, the SEREX method was the most successful approach for cloning immunogenic tumour ags recognized by B cells, and about 1700 genes have thus far been identified (Sahin et al, 1995(Sahin et al, , 1997Struss et al, 2001;Forti et al, 2002). Despite this wealth of tumour ags, only four SEREXdefined ags (tyrosinase, NY-ESO-1, coactosin-like protein and MAGE-1) were shown to elicit both cellular and humoral immune responses to tumour cells (Van der Bruggen et al, 1991;Brichard et al, 1993;Jager et al, 1998Jager et al, , 2000Nakatsura et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this wealth of tumour ags, only four SEREXdefined ags (tyrosinase, NY-ESO-1, coactosin-like protein and MAGE-1) were shown to elicit both cellular and humoral immune responses to tumour cells (Van der Bruggen et al, 1991;Brichard et al, 1993;Jager et al, 1998Jager et al, , 2000Nakatsura et al, 2002). Using SEREX, we recently demonstrated that fibulin-1 (Fbln-1) is a breast cancer-restricted ag able to induce specific antibody immunity that can be exploited as a tool for early detection of breast cancers (Forti et al, 2002;Pupa et al, 2002a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation